Practice of Buying and Selling Services Using the Instagram Application - Annisa Hafizhah; Firmansyah Firmansyah; Addys Aldizar (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2022)
This study aims to review fiqh on the practice of buying and selling transactions using deposit services on the Instagram application according to contemporary scholars, namely Erwandi Tarmizi, and Oni Sahroni This research uses the descriptive analysis method. Collecting data through interviews and literature study. The results of this study indicate that buying and selling transactions using deposit services on the Instagram application are viewed from the view of contemporary cleric Dr. Erwandi Tarmizi, MA, and Dr. Oni Sahroni, MA is allowed if the custodian pays first and then delivers the goods later.